2018
DOI: 10.1016/j.ebiom.2018.05.032
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Culture of Distal Airway Epithelial Cells Allows Differentiation Towards Alveolar Epithelial Cells Suited for Influenza Virus Studies

Abstract: As the target organ for numerous pathogens, the lung epithelium exerts critical functions in health and disease. However, research in this area has been hampered by the quiescence of the alveolar epithelium under standard culture conditions. Here, we used human distal airway epithelial cells (DAECs) to generate alveolar epithelial cells. Long-term, robust growth of human DAECs was achieved using co-culture with feeder cells and supplementation with epidermal growth factor (EGF), Rho-associated protein kinase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 67 publications
(85 reference statements)
0
15
0
Order By: Relevance
“…47,48 Overall, CR has been successful in generating several types of human tumor models and other human and mouse cell cultures used for various research purposes. [49][50][51][52][53][54] Therefore we anticipated that it could be useful for generating a valid patient-derived model for studying NB.…”
Section: Discussionmentioning
confidence: 99%
“…47,48 Overall, CR has been successful in generating several types of human tumor models and other human and mouse cell cultures used for various research purposes. [49][50][51][52][53][54] Therefore we anticipated that it could be useful for generating a valid patient-derived model for studying NB.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, when cultured at ALI in the presence or absence of BPAECs, the BATII cell line retains the ATII markers CD74 and SLC34A2 to a much greater degree than the B2AE cell line. Previous studies have reported that CD74 is lost quickly in the culture of primary ATII cells as they differentiate into ATI 2,53 . The BATII cell line appeared to retain expression of CD74 after two weeks culture at ALI, along with a pseudostratified morphology.…”
Section: Discussionmentioning
confidence: 93%
“…The alveolar epithelium is composed of two types of cell; alveolar type I (ATI) and alveolar type II (ATII). Alveolar type I cells cover 90 % of the alveolar surface 2 , despite only constituting in the region of 7 % of the epithelium by numbers 3 . This can be attributed to the elongated squamous cell morphology of the ATI, which spreads over a large surface area and lies in close proximity to capillary endothelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…These differentiated pneumocytes were amenable for genetic perturbation such as RNAi and supported influenza A virus replication. 45 Very recently, the same group showed that SARS-CoV-2 can bind to and successfully infect the DAEC-derived pneumocytes. Instead of using genetically transformed cell lines, these DAEC-derived pneumocytes can develop physiologically relevant cellular systems and give an authentic reflection of treatment with antiviral compounds.…”
Section: Physiologically Relevant In Vitro Models—mentioning
confidence: 99%